Association of Access to Family Planning Information and Unwanted Pregnancy (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Unwanted Pregnancy (UP) is a condition in which a partner or the opposite sex does not want a pregnancy or birth between partners. The incidence of Unwanted Pregnancy in Indonesia is still high (17.5%). Unwanted Pregnancy has an impact on the health of the mother, infant, and family problems. The study aimed to determine the relationship between access to information about family planning and Unwanted Pregnancy in Indonesia. This type of research is quantitative with a cross-sectional design using Program Performance and Accountability Survey 2019 secondary data. The independent variable is access to information about family planning with the dependent variable being Unwanted Pregnancy. Confounding variables are predisposing factors (age, education, occupation, parity, and marital status), enabling factors (area of ​​residence, socioeconomic status, family planning needs), and reinforcing factors (support from health workers). The sample of this study were women of childbearing age 15-49 years who were recorded as pregnant. Multivariate analysis using multivariate logistic regression. Results of this study show that there is a significant relationship between access to family planning information and UP in Indonesia, after controlling for confounding variables (p-value 0.001) (OR=1.964;95%CI:1.334-2.893). Health promotion efforts are needed through communication, information, and health education regarding the importance of access to information about family planning and UP so that it can influence the behavior of women of childbearing age in Indonesia.